Early programming of adult diseases in resource poor countries. Issue 4 (21st March 2005) - Prentice, A M; Moore, S E
Abstract : Considerable evidence now exists to suggest that early exposure to nutritional deprivation can have long term consequences to health, with low birth weight now considered a risk factor for later health outcomes such as coronary heart disease, stroke, type 2 diabetes, and the metabolic syndrome. Of importance, such effects are most exaggerated when faced with over-nutrition in later life, forming the basis for the "thrifty phenotype" hypothesis. The evidence in support of these associations comes largely from retrospective cohort studies in which adult outcomes were correlated with birth weight records. Relatively little data is available from developing countries, where long term record keeping of birth weight data has not been a high priority. Arguably however, such countries are at the greatest risk from the mismatch of early nutritional deprivation and later nutritional affluence. This paper explores the importance of the "developmental origins of health and disease" hypothesis in resource poor countries.